2020
DOI: 10.3390/ijms21124268
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of the Renin–Angiotensin System on the Endothelium in Vascular Dementia: Unresolved Issues and Future Perspectives

Abstract: The effects of the renin–angiotensin system (RAS) surpass the renal and cardiovascular systems to encompass other body tissues and organs, including the brain. Angiotensin II (Ang II), the most potent mediator of RAS in the brain, contributes to vascular dementia via different mechanisms, including neuronal homeostasis disruption, vascular remodeling, and endothelial dysfunction caused by increased inflammation and oxidative stress. Other RAS components of emerging significance at the level of the blood–brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 78 publications
(134 reference statements)
1
19
0
Order By: Relevance
“…Increasing amounts of evidence indicate that Ang II plays an important role in the initiation and progression of vascular endothelial dysfunction, inflammation and vascular remodelling [ 31 ]. Ang II–induced effects of hypertension on retinal vessels lead to vascular changes, including intimal hyperplasia, hyaline degeneration, endothelial cell barrier dysfunction and breakdown of the blood–retina barrier (BRB), which promote exudation of serum proteins and lipids into the retina, leading to fluid accumulation (oedema) in multiple layers of the retina [ [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing amounts of evidence indicate that Ang II plays an important role in the initiation and progression of vascular endothelial dysfunction, inflammation and vascular remodelling [ 31 ]. Ang II–induced effects of hypertension on retinal vessels lead to vascular changes, including intimal hyperplasia, hyaline degeneration, endothelial cell barrier dysfunction and breakdown of the blood–retina barrier (BRB), which promote exudation of serum proteins and lipids into the retina, leading to fluid accumulation (oedema) in multiple layers of the retina [ [32] , [33] , [34] ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the RAS dysregulation surpass the renal and cardiovascular systems to encompass other body tissues and organs, including the brain (Noureddine et al, 2020). Thus, it has been reported that SARS-CoV-2-infected patients can have a significant functional impairment of RAS (Osman et al, 2021;Wang et al, 2022a), which is a consequence of the binding of SARS-CoV-2' RBD of the viral S protein, precisely, the S1 subunit to the ACE2 enzyme in human cells.…”
Section: Systemic Renin-angiotensin System and Covid-19-associated Ne...mentioning
confidence: 99%
“…Mechanistically, endothelial cells, smooth muscle cells, glial cells, and neurons all utilize ACE2 for proper function [41] in many brain regions [43]. Consequently, brain levels of ACE2 are relevant for the degree of ischemic injury and its subsequent potential impact on neurodegeneration, Alzheimer’s disease (AD), and dementia risk [43-45]. ACE2 levels are accordingly inversely correlated with parenchymal amyloid beta and tau in AD [46].…”
Section: Sars-cov-2 General Infection Characteristicsmentioning
confidence: 99%